STRATEGI PENETAPAN TARIF RUMAH SAKIT BERDASARKAN UNIT COST - L. Ahmad Riofandi; Aufa Ardini; M. Yusuf Maulana; Haerani; Anisa Ekarina; Andina Salma A; Adrian Saputra; Lale Ajeng Khalifatun Wardani (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
Rate is one of the key elements that determines the sustainability of hospital management. Rational and proportional determination of rate will affect the quality of health services. This article aims to explore strategies for implementing hospital rates. This article is a research based on a literature review using the library method. The results show changes in the rates structure that comprehensively take into account unit cost, competitive position, ability to pay, willingness to pay, and strategic objectives, as well as the internal conditions of the hospital are very significant in helping to improve the financial structure of the hospital. Conversely, setting rates that only follow rates in other hospitals does not help hospitals improve their financial condition.